REDUKSI AKTIVITAS URANIUM DALAM LIMBAH RADIOAKTIF CAIR MENGGUNAKAN PROSES ELEKTROKOAGULASI - Prayitno; Ridantami, Vemi; Prayogo, Imam (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Waste generated from the process of the industrial material development one of which waste containing uranium radioactive, can have negative impact on humans and the environment. In the present time, chemicals are still mostly use in radioactive waste treatment. To reduce pollutants with the use of chemicals is less efficient, because less environmentally friendly, take long time and costly. Therefore, a system of electrocoagulation process will be applied to decrease the activity of uranium from waste solution. The purpose of this study is to determine the efficiency of uranium activity decrease in waste water which is produced in the electrolysis process is conducted with voltage variations, the dwelling time, electrode spacing, and the waste inlet pH. The waste that will be treated has uranium contaminant levels of 500 mg/L. The experiment was conducted by a batch system with aluminum electrodes. Parameters affecting electrocoagulation process, such as voltage, time, distance electrode, and the pH have been studied and the best voltage optimization condition has been obtained of 12.50 V, a distance of 1 cm, pH 7, and in the processing time of 60 minutes efficiency of 97.20 % was obtained.